2021
DOI: 10.3390/ijms22105180
|View full text |Cite
|
Sign up to set email alerts
|

CACNA1A Mutations Causing Early Onset Ataxia: Profiling Clinical, Dysmorphic and Structural-Functional Findings

Abstract: The CACNA1A gene encodes the pore-forming α1A subunit of the voltage-gated CaV2.1 Ca2+ channel, essential in neurotransmission, especially in Purkinje cells. Mutations in CACNA1A result in great clinical heterogeneity with progressive symptoms, paroxysmal events or both. During infancy, clinical and neuroimaging findings may be unspecific, and no dysmorphic features have been reported. We present the clinical, radiological and evolutionary features of three patients with congenital ataxia, one of them carrying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…On review of the latest literature in the EA, published since the closing date of our initial systematic literature review (April 2021–June 2022), we identified a total of nine related articles (Table S4). These reported on 10 patients with novel variants in the CACNA1A [19–29]. In a case report of CACNA1A ‐related EA, dalfampridine 0.3 mg/kg was shown to resolve falls that had been unresponsive to acetazolamide (treatment was delayed due to insufficient literature on the topic) [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On review of the latest literature in the EA, published since the closing date of our initial systematic literature review (April 2021–June 2022), we identified a total of nine related articles (Table S4). These reported on 10 patients with novel variants in the CACNA1A [19–29]. In a case report of CACNA1A ‐related EA, dalfampridine 0.3 mg/kg was shown to resolve falls that had been unresponsive to acetazolamide (treatment was delayed due to insufficient literature on the topic) [30].…”
Section: Resultsmentioning
confidence: 99%
“…Our review of the latest literature (April 2021–June 2022) revealed a total of two related articles (Table S4). These were reported on two patients with novel variants in the PDHA1 gene [19–29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an autopsy study in early-onset SCA6, Purkinje cells were found to have reduced dendritic mass and spines, as well as reduced dendritic branching complexity [ 25 , 26 ]. Recent studies have shown that patients with CACNA1A mutations exhibit atrophy of the cerebellum during development, which is a recognizable neurodevelopmental disorder [ 27 ].…”
Section: Increasing Evidence Linking Purkinje Cell Dendritic Developm...mentioning
confidence: 99%
“…The Voltage-dependent P/Q-type calcium channel subunit alpha-1A (CACNA1A) gene has been implicated in epileptic encephalopathy, familial hemiplegic migraine, episodic ataxia, and spinocerebellar ataxia [45,46] and has recently been reported in a small number of atypical Rett patients previously lacking known genetic mutations [47]. Voltage-sensitive calcium channels mediate the entry of calcium ions into excitatory neurons and are also involved in a variety of calcium-dependent processes, neurotransmitter release.…”
Section: Meta-analysis Hub Genes Within the Skyblue Module Are Releva...mentioning
confidence: 99%